Dynamic modelling in slopes using finite difference program - Dhakal, Subodh (Bulletin of the Department of Geology, 2009)
The finite difference program FLAC is used for dynamic modelling of slopes whereby the relationship of the slope geometry, earthquake input signals (mainly frequency of the wave) and the material properties with amplification of vibration on the surface are investigated. At the same time, the influence of varying input frequencies is also investigated. The higher slopes were amplified most by the lower input frequency whereas the reverse was true for the smaller slopes. The overall magnitude of the amplification was maximum with input signals of higher frequency and lower slope heights. The horizontal amplification as much as 17 (horizontal acceleration in the order of 1.7g) was obtained for the normal limestone slope with 20 m height when an input signal of 15 Hz frequency was applied. This experiment revealed that for extremely lower values of shear modulus, there was mostly attenuation instead of amplification and for extremely high values of shear modulus, amplification was negligible as compared to the certain range of intermediate shear modulus. Maximum amplification in the order of 6.5 (horizontal acceleration of 0.66g) was achieved for the shear modulus of 3000 MPa where slope height was of 40 m. doi: 10.3126/bdg.v12i0.2253 Bulletin of the Department of Geology, Vol. 12, 2009, pp. 88-94